2005
DOI: 10.1207/s15402010bsm0304_1
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sleep and Cortisol Responses to Stress in Children and Adolescents: A Pilot Study

Abstract: A growing body of animal and human research suggests reciprocal associations between sleep and activity of the hypothalamic pituitary adrenocortical (HPA) axis. However, few studies have examined associations between sleep and stress-induced cortisol responses in children and adolescents. This pilot study examined associations among 3 sleep parameters (sleep-wake behavior problems, daytime sleepiness, sleep quantity) and cortisol responses to stress in 31 participants ages 10 to 17 (15 males, 16 females). Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…32 Healthy individuals with lower cortisol responses to laboratory stressors have also been shown to have increased pain sensitivity to standardized challenges following the stressor. 33,34 A separate line of experimental research has demonstrated that poor sleep prior to physical 35 and psychological challenges results in reduced acute cortisol responses, 36,37 which appears to be selective for sleep the night immediately before the challenge. 36 Together, these studies raise the possibility that the physiological response to surgery stress may be important in the relationship between sleep and postoperative pain; although additional research on these mechanisms is clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…32 Healthy individuals with lower cortisol responses to laboratory stressors have also been shown to have increased pain sensitivity to standardized challenges following the stressor. 33,34 A separate line of experimental research has demonstrated that poor sleep prior to physical 35 and psychological challenges results in reduced acute cortisol responses, 36,37 which appears to be selective for sleep the night immediately before the challenge. 36 Together, these studies raise the possibility that the physiological response to surgery stress may be important in the relationship between sleep and postoperative pain; although additional research on these mechanisms is clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these deficits, long-term sleep deprivation has been reported to be associated with dysfunctional immune systems (Palma et al, 2007), particularly in depressive participants with sleep disturbance (Motivala et al, 2005). A recent experiment study by Capaldi et al (2005) revealed blunted cortisol reactivity to an experimental stressor among participants with poor self-reported sleep quality in comparison to those with better sleep quality, although self-reported sleep quantity (hours of sleep) was not related to cortisol activity. Wright et al (2007) also reported that individuals with objectively assessed poor sleep had a blunted response to the experimental stressor, although no associations were found between cortisol activity and self-reported sleep variables.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of evidence showing a close association between increased HPA SA and poor sleep, whether in healthy children [31,32] , adolescents [33] , adults [34] , infants suffering from infantile colic [35] or patients suffering from depressive symptoms [36][37][38] . Consequently, it is conceivable that a similar pattern may be found among adult meditators.…”
mentioning
confidence: 99%